Patterns of Complementary and Alternative Medicine Use among Psoriasis Patients in a Tertiary Care Hospital in South India – A Cross-sectional Study - Adithya Chandran; Saritha Mohanan; B Maharani (Clinical Dermatology Review)
Background: Complementary and alternative medicine (CAM) refers to medical practices that are not part of conventional medicine. Reports in literature suggest the prevalence of CAM use ranges from 37% to 87%. There are no data on frequency of CAM use in Indian patients with psoriasis. Materials and Methods: A descriptive study was designed to look at frequency of CAM use in psoriasis patients attending the DVL outpatient department of a tertiary care hospital in South India. The clinicoepidemiological details and details of CAM use were entered into a predesigned pro forma. Results: Ninety-six psoriasis patients were included in the study. CAM use was seen in thirty (31.58%) psoriasis patients. Siddha treatment was the most common CAM used. Statistical analysis showed significant association of gender (male > female), time since diagnosis, alcohol use, and Psoriasis Area and Severity Index (PASI) score with use of CAM. Logistic regression analysis found age, education, socioeconomic status, alcohol use, time since diagnosis, presence of concomitant disease, affordability of medication, and PASI score to be independent predictors of CAM use. Limitations: The limitations of our study were the small sample size and lack of emphasis on dietary modifications followed. Conclusion: CAM is used by approximately 30% of psoriasis patients in South India, and the most common therapy used is Siddha. Knowledge of evidence regarding CAM therapies will help the dermatologist offer a balanced view of risks and benefits of indigenous CAM practices to our patients.